1994
DOI: 10.1099/00221287-140-3-631
|View full text |Cite
|
Sign up to set email alerts
|

Presence in rumen bacterial and protozoal populations of enzymes capable of degrading fungal cell walls

Abstract: Ruminal bacteria and protozoa, and cell-free rumen fluid, were tested for the presence of enzymes involved in the degradation of the fungal cell wall. Protozoal homogenate obtained by ultrasonication showed chitinase (EC 3.2.1.14) and N-acetyl-/&glucosaminidase (EC 3.2.1.52) activities when assayed with f luorogenic 4-methylumbel liferyl substrates. The chitinase activity was predominantly of the 'exo'-type. Lysozyme (EC 3.2.1 .17) and 1,3-~glucanase (EC 3.2.1.39) activities were also present in this fraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
3
39
1
1
Order By: Relevance
“…This may have been caused by different concentrations of protein in the crude enzyme preparation, as well as the condition of the protozoa after incubation with antibiotics. Similar results of enzymatic studies were obtained by Morgavi et al (1994b). However, it should be noted that the cited authors worked on a mixed population of protozoa and used specific substrates to determine exochitinolytic activity.…”
Section: Discussionsupporting
confidence: 69%
“…This may have been caused by different concentrations of protein in the crude enzyme preparation, as well as the condition of the protozoa after incubation with antibiotics. Similar results of enzymatic studies were obtained by Morgavi et al (1994b). However, it should be noted that the cited authors worked on a mixed population of protozoa and used specific substrates to determine exochitinolytic activity.…”
Section: Discussionsupporting
confidence: 69%
“…Growth rates were determined by Klett meter readings of liquid cultures incubated at various temperatures. Four distinct extracellular enzyme activities were assayed, between 2° and 37°C, as follows: (1) protein hydrolysis was detected by clearing zones on DMB agar with skim milk added (15 g/L) (Lichenstein et al, 1992); (2) esterase activity was detected by precipitation zones on DMB agar supplemented with 1% Tween-20 (ICN Biomedicals) (Jensen, 1983); (3) chitin hydrolysis was detected by clearing zones on DMB agar containing colloidal chitin (15g/L) (Lingappa and Lockwood, 1961;Morgavi et al, 1994); and (4) starch hydrolysis was indicated by clear zones on iodine-stained DMB agar with starch (15g/L).…”
Section: Jf Biddle Et Al Enrichment and Cultivation Of Microorganimentioning
confidence: 99%
“…Coincubations of protozoa with fungi have shown that the protozoa are able to both ingest and digest fungi (47). Morgavi et al (37) found considerable chitinase activity in samples of mixed rumen protozoa, which would account for their predatory activity on the rumen fungi (30,54). No effects were noted when a washed preparation of small protozoa (over 95% Dasytricha ruminantium) was incubated with the rumen fungus Neocallimastix frontalis.…”
mentioning
confidence: 99%